Current Issues in the Implementation of English Language Subjects in Elementary Schools: - - Amalia, Arsyi Rizqia; Edwita²; Yatimah³, Durotul (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
The aim of this research is to identify the English language skills of junior high school students who have just graduated from elementary school, as well as identify problems in implementing English language learning in elementary school. This research was motivated by the interview result with junior high school teachers who stated that there are a big differences in English language skills among students who had just graduated from elementary school which became an obstacle in learning English process in junior high school, this was believed to occur due to issues in implementing English language learning in elementary school. This research used a mixed method with a research sample of 150 students from two junior high schools in the Sukabumi City and Sukabumi Regency areas. The results of this research show that the English language skills of students both in the city and regency show that more than 50% of students scored below 60 and fall into the category of very low English skills. This study reveals that English language education in elementary schools faces various challenges, including inconsistencies in the quality of English language teaching, gaps in access to English language teachers, limited use of teaching materials, learning methods and media. Despite these challenges, there is a high level of interest in English among students, indicating that with the right support, the implementation of English subject in elementary school will be better.